2008
DOI: 10.1007/s10350-008-9224-5
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Adenomas in Young Patients: Microsatellite Instability is not a Useful Marker to Detect New Cases of Lynch Syndrome

Abstract: Adenomas diagnosed before aged 40 years presented microsatellite instability only in patients from families with clinical criteria for Lynch syndrome. According to our results, to detect new cases of Lynch syndrome, family history is more important than microsatellite instability testing in adenomas from young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Follow-up studies revealed this patient to be an MSH6 mutation carrier (case 3 in Table 3). While the evidence for testing polyps is equivocal [25][26][27], this case demonstrates that it may be warranted if there is an indication of family history of cancer.…”
Section: Discussionmentioning
confidence: 80%
“…Follow-up studies revealed this patient to be an MSH6 mutation carrier (case 3 in Table 3). While the evidence for testing polyps is equivocal [25][26][27], this case demonstrates that it may be warranted if there is an indication of family history of cancer.…”
Section: Discussionmentioning
confidence: 80%
“…A limitation of the study is that it does not provide any information on the usefulness of adenoma immunohistochemistry as a screening test for young onset population-based adenomas. A previous study has suggested that an approach using microsatellite instability as a screening test is likely to produce a low yield 9 . The increasing recognition of the role of family history in determining risk has lead to increased colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Today, screening for Lynch syndrome can be achieved through immunostaining for mismatch repair proteins in a spectrum of Lynch syndrome-associated cancers including those of the colorectum, but it remains unclear if screening of colonic adenomas is of value for the idenitification of patients with Lynch syndrome. Screening of early-onset adenomas for mismatch repair deficiency in order to diagnose Lynch syndrome in the population has yielded disappointing results 9 , suggesting that more focused testing should be evaluated. Not all Lynch syndrome adenomas found in mismatch repair mutation carriers show loss of immunostaining, and there is considerable variation in the literature about the frequency of loss of mismatch repair protein expression in this setting 8, 1013 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical suspicion is of paramouth importance in the diagnosis of LS. Moreover, Ferreiara reported that to detect new cases of LS, family history is more important than microsatellite instability testing for adenomas of young patients (23). There is potentially a high risk of metachronous colorectal cancer if an initial cancer in a LS patient (defined according to Amsterdam criteria) is treated by partial colectomy.…”
Section: Discussionmentioning
confidence: 99%